Cytotoxic coumaronochromones from the inflorescences of Celosia cristata. Issue 16 (18th August 2017) - Yan, He; Zhang, Gonghai
Abstract: Investigation on the MeOH extracts of the inflorescences of Celosia cristata led to the isolation of two new coumaronochromones, cristatone I (1 ) and cristatone II (2 ), along with three known flavones (3 –5 ). Their structures were elucidated on the basis of spectroscopic analyses. Compounds1 –5 were tested for their cytotoxic activity against HeLa and BGC-823 cancer cell lines, of which cristatone II (2 ) showed interesting activity with the IC50 value of 23.82 μM. Abstract :